Cross-reaction of POC-CCA urine test for detection of Schistosoma mekongi in Lao PDR: a cross-sectional study - Anousin Homsana; Peter Odermatt; Phonesavanh Southisavath; Aya Yajima; Somphou Sayasone (BMC, 2020)
Abstract Background The point-of-care circulating cathodic antigen (POC-CCA) test is increasingly used as a rapid diagnostic method for Schistosoma mansoni infection. The test has good sensitivity, although false positive results have been reported among pregnant women and patients with urine infections and hematuria. We validated the POC-CCA test's ability to diagnose Schistosoma mekongi infection in Lao People's Democratic Republic (Lao PDR), where S. mekongi is endemic. Of particular interest was the test's specificity and possible cross-reactivity with other helminth infections. Methods We conducted a cross-sectional study of children and adults in the provinces of Champasack (Schistosoma mekongi and Opisthorchis viverrini endemic), Savannakhet (O. viverrini endemic) and Luang Prabang (soil-transmitted helminths endemic) between October 2018 and April 2019. POC-CCA and urine dipstick tests were administered to all study participants, while an additional pregnancy test was offered to women. Two stool samples were collected from participants and examined with a Kato-Katz test (two smears per stool). Logistic regression was used to associate potential confounding factors (predictors) with POC-CCA test results (outcome). Results In S. mekongi-endemic Champasack, 11.5% (n = 366) and 0.5% (n = 2) of study participants had positive POC-CCA and Kato-Katz test results, respectively. Only one of the two Kato-Katz positive patients was also POC-CCA positive. In Champasack and Luang Prabang, where S. mekongi is not endemic, the POC-CCA test yielded (presumably) false positive results for 6.0% (n = 22) and 2.5% (n = 9) of study participants, respectively, while all of the Kato-Katz tests were negative. POC-CCA positive test results were significantly associated with O. viverrini infection (1.69, 95% confidence interval (CI): 1.02-2.77, P = 0.042), increased leukocytes (adjusted Odds Ratio (aOR) = 1.58, 95% CI: 1.15-2.17, P = 0.005) and hematuria (aOR = 1.50, 95% CI: 1.07-2.10, P = 0.019) if the observed trace was counted as a positive test result. Two pregnant women from Champasack province had POC-CCA positive tests. Conclusions We observed a cross-reaction between the POC-CCA test and O. viverrini infection. To some extent, we can confirm previous observations asserting that POC-CCA provides false positive results among patients with urinary tract infections and hematuria. In S. mekongi-endemic areas, POC-CCA can be applied cautiously for surveillance purposes, keeping in mind the considerable risk of false positive results and its unknown sensitivity.